Awareness on the good Indoor Air Quality (IAQ) at Alam Perdana, Selangor double storey terrace house / Nurul Bahriah Badriah Abdul Kahar and Irwan Mohammad Ali - Abdul Kahar, Nurul Bahriah Badriah; Mohammad Ali, Irwan (2023)
This study examines the indoor air quality (IAQ) awareness among residential area occupants, aiming to identify the factors contributing to occupants' discomfort and their understanding of good IAQ characteristics. The research revealed that a significant majority of respondents experienced discomfort in their homes due to inadequate IAQ, attributed to insufficient temperature regulation, ventilation issues, and potential sick building syndrome, leading to various health-related symptoms. The results highlighted a concerning lack of knowledge about IAQ among the respondents, with a majority unaware of the factors influencing indoor air quality and the characteristics of good IAQ. Specifically, residents of Alam Perdana demonstrated limited familiarity with the distinguishing features of satisfactory IAQ, posing challenges in differentiating between acceptable and poor air quality within their living spaces. In conclusion, this research emphasized the importance of IAQ awareness among residential occupants, suggesting the need for educational initiatives to enhance understanding and improve indoor air quality conditions. By increasing IAQ awareness, residents can take proactive measures to create healthier living environments and elevate their overall well-being.